Bowstring winter - "Hazarika, Dhruba" (Gurgaon, 2006)
Set against the lush landscape of Shillong, Dhruva Hazarika's tale of revenge and violence brilliantly evokes the sights and smells of north-east India while narrating a dynamic tale which addresses the universal themes of friendship, loyalty and the inherent loneliness of man.
Keywords: Fiction